Mammalian PNLDC1 is a novel poly(A) specific exonuclease with discrete expression during early development. Issue 18 (11th August 2016) - Anastasakis, Dimitrios; Skeparnias, Ilias; Shaukat, Athanasios-Nasir; Grafanaki, Katerina; Kanellou, Alexandra; Taraviras, Stavros; Papachristou, Dionysios J.; Papakyriakou, Athanasios; Stathopoulos, Constantinos
Abstract : PNLDC1 is a homologue of poly(A) specific ribonuclease (PARN), a known deadenylase with additional role in processing of non-coding RNAs. Both enzymes were reported recently to participate in piRNA biogenesis in silkworm and C. elegans, respectively. To get insights on the role of mammalian PNLDC1, we characterized the human and mouse enzymes. PNLDC1 shows limited conservation compared to PARN and represents an evolutionary related but distinct group of enzymes. It is expressed specifically in mouse embryonic stem cells, human and mouse testes and during early mouse embryo development, while it fades during differentiation. Its expression in differentiated cells, is suppressed through methylation of its promoter by the de novo methyltransferase DNMT3B. Both enzymes are localized mainly in the ER and exhibit in vitro specificity restricted solely to 3′ RNA or DNA polyadenylates. Knockdown of Pnldc1 in mESCs and subsequent NGS analysis showed that although the expression of the remaining deadenylases remains unaffected, it affects genes involved mainly in reprogramming, cell cycle and translational regulation. Mammalian PNLDC1 is a novel deadenylase expressed specifically in cell types which share regulatory mechanisms required for multipotency maintenance. Moreover, it could be involved both in posttranscriptional regulation through deadenylation and genome surveillance during early development.